Self-concepts applied as a strategy to measure the level of acceptance of a Serious Game - Anthony Lins; Walter Franklin Marques Correia; Fábio Ferreira da Costa Campos; Marnix van Gisbergen; João Marcelo Xavier Natário Teixeira (Journal on Interactive Systems)
This paper explores the application of Self-Concepts, a Semantic-Differential Scale-based methodology, to evaluate a Serious Game designed for cognitive impairment assessment using the MoCA test and augmented reality (AR) for mobility analysis. A case study involved seven elderly participants. Despite some challenges in navigating the AR environment and cognitive tests, self-concept evaluations consistently demonstrated high user expectations and positive experiences with the digital artifact. This study validates the process and highlights the potential of Self-Concepts in assessing product acceptance within user groups.